Isokinetic Strength and Work Capacity of Human Muscles after a Spaceflight - A.Koryak, Yuri (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The effects of long-term (213.0  30.5 days) aboard the Mir station and short-term (10 days) spaceflights aboard the International Space Station (ISS) on the joint torques of various muscles and work capacity of knee extensors were studied in male cosmonauts. Joint torque and muscle endurance testing was performed 30 days before and 3–5 days after a spaceflight, using a LIDO Multi-Joint Isokinetic Rehabilitation System (USA). Greater postflight changes in maximal joint torque were observed for back, knee, and ankle extensors compared with flexors, and the difference was especially clearly seen after long-term spaceflights. Muscle work capacity was inferred from the gradient of declining muscle force produced in a series of rhythmic voluntary concentric movements and was found to decrease after both short- and long-term spaceflights. The area under the muscle contraction curve decreased to a greater extent and in all regions of the curve after long-term spaceflights. The finding that the contractile functions and work capacity of muscles decrease more after long-term than after short-term spaceflights in spite of the physical training program of a certain type gave grounds to assume that physical training employed in longterm spaceflights were insufficient to simulate the daily mechanical load that the cosmonauts had before a spaceflight.